1986
DOI: 10.1266/jjg.61.79
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism and evolution in parthenogenetic animals. XIII. Changes in the degree of polyploidy in Curculionidae.

Abstract: Tetraploid and pentaploid individuals of Catapionus gracilicornis from Temma, Aomori Prefecture as well as triploid and hexaploid individuals of Blosyrus japonicus from Ishiyama-rikkyo, Hokkaido, have been assayed by starch gel electrophoresis. All weevils were parthenogenetic females. There was some variation within parthenogenetic populations. On the other hand, different degrees of polyploidy within a species were identical over all but one enzyme locus assayed. This is taken as further evidence to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The presence of several unique copies of submetatric chromosomes (N° 6a and b, 7a and b, and 8a) may support such a scenario. The second hypothesis proposes that several "hybridization" events can generate the polyploid karyotypes of parthenogenetic species (Takenouchi et al, 1986), which was demonstrated for a curculionid beetle using molecular analyses (Tomiuk & Loeschke, 1992). Unfortunately, in these studies, only the number of chromosomes was counted.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of several unique copies of submetatric chromosomes (N° 6a and b, 7a and b, and 8a) may support such a scenario. The second hypothesis proposes that several "hybridization" events can generate the polyploid karyotypes of parthenogenetic species (Takenouchi et al, 1986), which was demonstrated for a curculionid beetle using molecular analyses (Tomiuk & Loeschke, 1992). Unfortunately, in these studies, only the number of chromosomes was counted.…”
Section: Discussionmentioning
confidence: 99%